2007
DOI: 10.1681/asn.2006030221
|View full text |Cite
|
Sign up to set email alerts
|

Urinary N-Acetyl-β-(D)-Glucosaminidase Activity and Kidney Injury Molecule-1 Level Are Associated with Adverse Outcomes in Acute Renal Failure

Abstract: The role of urinary biomarkers of kidney injury in the prediction of adverse clinical outcomes in acute renal failure (ARF) has not been well described. The relationship between urinary N-acetyl-␤-(D)-glucosaminidase activity (NAG) and kidney injury molecule-1 (KIM-1) level and adverse clinical outcomes was evaluated prospectively in a cohort of 201 hospitalized patients with ARF. NAG was measured by spectrophotometry, and KIM-1 was measured by a microsphere-based Luminex technology. Mean Acute Physiology, Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
331
0
24

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 482 publications
(361 citation statements)
references
References 30 publications
6
331
0
24
Order By: Relevance
“…A sensitive high-throughput method has been developed to quantify urinary Kim-1 by a sandwich ELISA and now a Luminex-based bead assay (Liangos et al, 2007). Another methodological advantage of Kim-1 is that it is stable in urine and no stabilizing buffer needed for the collected urine samples prior to freezing and storage for later analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A sensitive high-throughput method has been developed to quantify urinary Kim-1 by a sandwich ELISA and now a Luminex-based bead assay (Liangos et al, 2007). Another methodological advantage of Kim-1 is that it is stable in urine and no stabilizing buffer needed for the collected urine samples prior to freezing and storage for later analysis.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Several small studies have found that a range on novel kidney injury-specific biomarkers, including urinary cystatin C, a1-microglobulin, N-acetylbeta-(D)-glucosaminidase, and retinol-binding protein correlate with severe AKI requiring RRT in hospitalized patients. 29,31,32 Overall, these candidate biomarkers are very promising; however, currently they are not widely available. It is probable that these biomarkers, either as a panel or coupled with clinical variables, will further enhance our capacity for early diagnosis and prognosis of AKI.…”
Section: Acute Kidney Injury Predictionmentioning
confidence: 99%
“…These include N-acetyl-␤-D-glucosaminidase (NAG), neutrophil gelatinase associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), cystatin C, and IL-18 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, there are no previously reported data for the temporal expression pattern of urinary KIM-1 and NAG before the development of AKI in adult patients.…”
mentioning
confidence: 99%